PENGEMBANGAN BAHAN AJAR BERBASIS STEM (SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS) MATERI KELISTRIKAN UNTUK SEKOLAH DASAR - Yuanita, Yuanita; Kurnia, Feni (Profesi Pendidikan Dasar, 2019)
This research aims to develop STEM (Science, Technology, Engineering, And Mathematics) based teaching material of electrical material for primary schools. This R D study used 4D design; Define, Design, Develop and Disseminate. The instruments used are documentation, expert validation sheet, interview sheet, and feasibility test. Based on the first stage of the development; curriculum analysis, materials, and teaching materials, the second stage; specification of teaching materials design, the third stage; content analysis trhough construct validation with percentage value; 97% of the first material validator, 80% of second material validator, 82% of media validator, and 92% of language validator. The test was done to the small and huge scales of the sixth grade elementary school students with each average value was 96% and 99%. As the teaching materials user, teachers’ testing response was conducted at the fourth stage with the average value of 100%. Based on the results above, it can be summed up that the STEM – based teaching materials with high feasibility can be used for learning teaching materials.